Quasioptical System for Corneal Sensing at 220-330 GHz: Design, Evaluation, and Ex Vivo Cornea Parameter Extraction - Tamminen, Aleksi; Palli, Samu-Ville; Ala-Laurinaho, Juha; Salkola, Mika; Raisanen, Antti V.; Taylor, Zachary D. (IEEE transactions on terahertz science and technology, 2021)
The design, simulation, and characterization of a quasioptical system for submillimeter-wave quantification of corneal thickness and water content are presented. The optics operate in the 220-330 GHz band and are comprised of two, custom aspheric, biconvex lenses in a Gaussian beam telescope configuration. The design produces broadband wavefront curvature matching to 7.5 mm radius of curvature target surfaces thus emulating a plane-wave-on-planar-media condition and enabling application of stratified medium theory to data analysis. Aspheric lens coefficients were optimized with geometric ray tracing subject to optical path length penalties and physical-optics simulations showed aspheric designs achieved wavefront coupling to spherical surfaces, superior to equivalent, canonical hyperbolic lenses. The fabricated lens system was characterized in a planar near-field scanner system and demonstrated good agreement to physical-optics simulations. An average central corneal thickness of 652 μ m and free water content volume of 47% were extracted from ex vivo sheep corneas via complex s -parameters and agree with literature values. Extracted contact lens thickness and water content agreed with independently validated values. Moreover, the quasioptical system enabled observation of dynamic changes in artificial tear-film, thickness, and water content. This work elucidates two major findings related to submillimeter-wave wavefront matching on spherical surfaces, with wavelength order radii of curvature: 1) An asphere whose sag coefficients are optimized via field phase variation on a spherical surface produces coupling superior to a plano-hyperbolic lens. 2) For most feasible apertures, the Gaussian beam waist is located in the aperture near field, suggesting consideration for operating in the beam near field.